Pembuatan Website dan Media Sosial Terverifikasi sebagai Media Promosi di SMK NU Kabat Banyuwangi - Febrian, Ayu Wanda; Prasetyo, Junaedi Adi; Amalia, Firda Rachma; Gibrilia, Nezza; Firmansah, Mohamad Agus (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
NU Kabat Vocational School is one of the educational institutions at the SMK (Vocational High School) level in Kabat District, Banyuwangi Regency. This school is relatively new, considering that it has only been 8 (eight) years since it was founded in 2015. It is known that SMK NU Kabat does not yet have a website as a means of digital school information. During that time, the school only relied on social media in the form of Instagram, Facebook and YouTube which did not optimally and professionally display school activities visually. In today's digital era, it is important to have a school website as a medium to promote and provide the latest information regarding school operations. This is to build a narrative of progress and convey the success of the school's performance. The aim is to increase public confidence in the existence of schools. Apart from that, it is also to follow the development of information technology in the world of education, which is currently showing quite significant changes. Having a website as a medium for disseminating information and promotions is one way that is relevant and efficient nowadays.